2009
DOI: 10.1007/s10615-009-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative Practice and Alternative Sexual Orientations: Helping Clients Navigate the Coming Out Process

Abstract: Those who differ from the dominant heterosexual ideal of exclusively other-sex attraction and intimacy encounter unique challenges, such as the coming out process, during which individuals with alternative sexual orientations must explore, define, and disclose their orientations in a way straight individuals need not. This article focuses on how clinicians can aid clients throughout the coming out process in a way that affirms the full range of sexual orientations. Following an overview of alternative sexual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…Family, then, is often the last to know (Goffman 1963:65). Research into the coming-out process among gays has indicated that coming out to parents is the most challenging, but also most definitive, moment in the coming-out process (Hill 2009:353, Carnelley et al 2011.…”
Section: Community Interests and Concernsmentioning
confidence: 99%
“…Family, then, is often the last to know (Goffman 1963:65). Research into the coming-out process among gays has indicated that coming out to parents is the most challenging, but also most definitive, moment in the coming-out process (Hill 2009:353, Carnelley et al 2011.…”
Section: Community Interests and Concernsmentioning
confidence: 99%
“…Heterosexism refers to the normalization of heterosexuality and the subsequent devaluation or invisibility of nonheterosexual sexualities (Herek, 2004;Hill, 2009;Hyman, 2008). Fish (2008) further conceptualized heterosexism into three domains: normalizing heterosexuality (the view of heterosexuals as superior and normal); compulsory heterosexuality (the "assumption that everyone is, or should be, heterosexual," p. 186); and the intersectional nature of heterosexism with other oppressions such as racism.…”
mentioning
confidence: 99%
“…Such approaches take into account fluid sexual identities rather than discrete categories of sexual orientation, as well as the experiences of individuals with other forms of discrimination and stigma due to gender, ethnicity, ability, and so forth (Hill, 2009). To be effective, practitioners must learn to challenge their own biases and assumptions about sex and gender norms, sexuality, and other identities (e.g., religious, ethnocultural) to support clients in exploring, understanding, and defining their own feelings, behaviors, and preferences (Hill, 2009;Langdridge, 2007;LaSala, 2006). Gay affirmative practice models operate from a person-in-environment perspective, focus on validating clients' sexual minority identity, and help clients to challenge internalized homophobia and to develop positive LGBQQ identities (Crisp, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These were key ideas presented in relation to how their family relationships influenced sexuality communication. Researchers advocate for a client-counsellor setting that supports the exploration of experiential nature of relationships (Hill, 2009;Maree & Pollard, 2009;Mollen & Staub, 2010;Neimeyer, 2006), including a strengths-based approach to goal-setting that frames the client in their own unique context (Mclnerney, 2007;Shade, 2006;te Riele, 2010). The stories presented here support the recommendations of these researchers working within a client-centered framework.…”
Section: Implications Of Beforeplaymentioning
confidence: 54%